2010
DOI: 10.1021/jf1038037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Commercial Grape Seed Tannins on Phenolic Composition, Chromatic Characteristics, and Antioxidant Activity of Red Wine

Abstract: The effect of addition of grape seed tannins on the phenolic composition, chromatic characteristics, and antioxidant activity of red wine was studied. Two highly pure commercial grape seed tannins (GSE100 and GSE300) were selected, and their phenolic compositions were determined. Two types of red wines were made with Castelão/Tinta Miúda (3/2, w/w) grapevine varieties by fermentation on skin using two different maceration times, which correspond to the wines rich and poor in polyphenols, respectively. Each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The addition of oenological tannins to wine during bottle aging maintained the highest value of colour intensity and of the concentration of anthocyanins, hydroxycinnamic esters, flavonols and tannin compared with that of other winemaking procedures, such as partial running-off of the must prior to fermentation and the addition of macerating enzymes. The addition of grape seed tannins increased the antioxidant activity of wines poor in phenolic substances (Neves et al 2010), while other studies have demonstrated that the estimated antioxidant activity of musts and wines, enriched by oenological tannins, was dependent on the method applied (Baiano et al 2009). The impact of the addition of oenological tannin on wine composition has been evaluated through sensory attributes (colour, astringency, aroma and mouthfeel), the composition of phenolic substances and antioxidant capacity (Harbertson et al 2012, Versari et al 2013).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The addition of oenological tannins to wine during bottle aging maintained the highest value of colour intensity and of the concentration of anthocyanins, hydroxycinnamic esters, flavonols and tannin compared with that of other winemaking procedures, such as partial running-off of the must prior to fermentation and the addition of macerating enzymes. The addition of grape seed tannins increased the antioxidant activity of wines poor in phenolic substances (Neves et al 2010), while other studies have demonstrated that the estimated antioxidant activity of musts and wines, enriched by oenological tannins, was dependent on the method applied (Baiano et al 2009). The impact of the addition of oenological tannin on wine composition has been evaluated through sensory attributes (colour, astringency, aroma and mouthfeel), the composition of phenolic substances and antioxidant capacity (Harbertson et al 2012, Versari et al 2013).…”
Section: Introductionmentioning
confidence: 92%
“…In fact, some work has shown that oenological tannins should be used with great care because depending on the characteristics of the tannin extract and its composition and concentration of phenolic substances, the addition may not improve wine composition and may even have a negative effect on it (Bautista-Ortin et al 2005, Cliff et al 2012, Harbertson et al 2012). In this context, some studies have been conducted to evaluate the effect of the addition of oenological tannins during prefermentation and postfermentation steps of winemaking and during bottle aging (Bautista-Ortin et al 2005, Parker et al 2007, Baiano et al 2009, Neves et al 2010, Gambacorta et al 2011, Canuti et al 2012). In this context, some studies have been conducted to evaluate the effect of the addition of oenological tannins during prefermentation and postfermentation steps of winemaking and during bottle aging (Bautista-Ortin et al 2005, Parker et al 2007, Baiano et al 2009, Neves et al 2010, Gambacorta et al 2011, Canuti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this decrease could be the release of gallic acid from polymeric PAs during storage as has been suggested by Nevest et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, a variety of HPLC detector types have been used including UV, Diode Array, Mass Spec and fluorescence [23-27]. The choice of fluorescence detection is within established analytical parameters for this determination as it offers selectivity and sensitivity for these compounds with the identity of the peaks being established by the use of authentic standards.…”
Section: Resultsmentioning
confidence: 99%